MENGURAI PROBLEMATIKA GENDER DAN AGAMA - Siti Zubaedah (Yinyang: Jurnal Studi Islam Gender dan Anak, 2015)
Gender issues became an important agenda of all parties because the reality of gender differences has implications fordifferences in status, roles and responsibilities between men and women that create gender inequality or discrimination or oppression. Theseinjustices can occur in various areas of life, both in the domestic area or the public, in education, health, security, economic, political, anddevelopment more broadly. This problem of gender inequality in many cases become an issue quite sensitive and not easily solved,especially when associated with religious doctrine, even as if the theological legitimacy